USP47-Mediated Deubiquitination and Stabilization of TCEA3 Attenuates Pyroptosis and Apoptosis of Colorectal Cancer Cells Induced by Chemotherapeutic Doxorubicin - Hou, Xiaodan; Xia, Jun; Feng, Yuan; Cui, Long; Yang, Yili; Yang, Peng; Xu, Xin (Frontiers in Pharmacology, 2021)
The ubiquitin–proteasome system regulates a variety of cellular processes including growth, differentiation and apoptosis. While E1, E2, and E3 are responsible for the conjugation of ubiquitin to substrates, deubiquitinating enzymes (DUBs) reverse the process to remove ubiquitin and edit ubiquitin chains, which have profound effects on substrates’ degradation, localization, and activities. In the present study, we found that the deubiquitinating enzyme USP47 was markedly decreased in primary colorectal cancers (CRC). Its reduced expression was associated with shorter disease-free survival of CRC patients. In cultured CRC cells, knockdown of USP47 increased pyroptosis and apoptosis induced by chemotherapeutic doxorubicin. We found that USP47 was able to bind with transcription elongation factor a3 (TCEA3) and regulated its deubiquitination and intracellular level. While ectopic expression of USP47 increased cellular TCEA3 and resistance to doxorubicin, the effect was markedly attenuated by TCEA3 knockdown. Further analysis showed that the level of pro-apoptotic Bax was regulated by TCEA3. These results indicated that the USP47-TCEA3 axis modulates cell pyroptosis and apoptosis and may serve as a target for therapeutic intervention in CRC.